On the text-external history of the copies of the Old Prussian Enchiridion - Dini, Pietro U. (Baltistica, 2024)
This contribution is devoted to a hitherto neglected topic in Old Prussian research: the external history of the four known copies of the Enchiridion (B1, B2, D, VH) and the reconstruction of movements to safeguard them during the Second World War and then from library to library up to their current location.